Impact of Emotional Needs on Intention to Stay and the Mediating Role of Perceived Organizational Support.an Empirical Study of Gen Y Employees’ in the Banking Sector in Malaysia - Zabedah Othman,; Jugindar Singh Kartar Singh,; Raemah Abdullah Hashim, (2019)
It is anticipated that over the next 10 years, the banking sector would require a workforce of about 200,000. Gen Y employees makes up about 40% of the current workforce in Malaysia. This number is expected to increase to 75% within a relatively short span of time. The present study examined the influence of emotional needs of Gen Y employees towards intention to stay and the mediating role of perceived organizational support. This was a quantitative research that used a survey method. Data was collected from a sample of 470 Gen Y employees in the banking sector in Malaysia. The findings revealed that emotional needs had a significant impact on intention to stay. Perceived organizational support was found to mediate the relationship between the two. The findings have significantly contributed to the advancement of knowledge in the emotional needs and intention to stay of Gen Y employees in the banking sector. The significant and positive impact of emotional needs and perceived organizational support suggests the importance of these factors in retention of Gen Y employees. The paper's primary contribution is that it provides an understanding that emotional needs and the mediating role of perceived organizational support have an impact on improving the intention to stay of Gen Y employees in the banking sector in Malaysia. From the practical implications perspective, organizations need to implement policies and procedures to help lessen employees quitting intentions. The results of this study suggest that organizations can implement policies covering the employee emotional needs and employees’ perception that their work and contributions are valued. With current trends of globalizations and diversity, the finding of this study can be beneficial to improve retention of Gen Y employees in other countries. (Abstract by authors)